Land use efficiency of sweet corn intercropping with different cowpea planting dates - Sumarni, Titin; Anggoro, Ariek Dwi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2024)
Cultivation of cowpea and sweet corn can optimize land use through an intercropping system, however, the planting date on intercropping is rarely evaluated. The research aimed to evaluate land use efficiency in sweet corn intercropping of different planting dates of cowpea. This research was conducted from January to May 2024 in Bocek Village, Malang, East Java. The study used a randomized complete block design with a single factor consisting of 7 levels, i.e., monoculture sweet corn, and sweet corn intercropping with different cowpea planting dates (0, 7, 14, 21, 28, and 35 days after sweet corn planting (DAP). Plant growth, yield, land equivalent ratio (LER), and area time equivalent ratio (ATER) were evaluated. The results showed that the intercropping sweet corn and cowpea planted at 21 DAP produced a higher yield than other planting dates. The highest LER of 1.96 and ATER of 1.93 was achieved in the sweet corn with cowpea planted at 21 DAP, indicating the highest land use efficiency occurred at the planting date of cowpea 21 days after planting sweet corn. Keywords: ATER; cropping system; LER; planting time; Vigna unguiculata; Zea mays